Analisis Pemilihan Rute Evakuasi Menggunakan Metode AHP Di Kawasan Rawan Bencana Merapi - Fida Ismaili, Abul; Eka Apsari, Ayudyah; Wahyu Adhi, Bagas; Wahyu Hidayat, Dwi (Jurnal Keselamatan Transportasi Jalan (Indonesian Journal of Road Safety), 2024)
Evacuation routes are important component during evacuation process, but sometimes the evacuation route conditions are not ready to use for evacuation. The good evacuation route can be seen from various aspects including width, pavement conditions and associated with the load or density during the evacuation process. An evacuation route need to optimize, but it is very difficult, due to time and cost constraints that cause not all available routes become good choices during evacuation. So it is necessary to select a good route for evacuation. In this study, the best evacuation routes are select using AHP method to analyze the priority of evacuation route. The criteria including the shortest distance and pavement conditions. Of the 20 available routes, seven routes are becomes recommended evacuation route. This research provides practical recommendations for improving road conditions and increasing capacity on specific routes to enhance evacuation efficiency in the disaster-prone areas of Merapi.